Strategi Dan Implementasi Kebijakan Imigrasi Indonesia Dalam Menanggulangi Penyelundupan Manusia: Analisis Terpadu Terhadap Efektivitas, Tantangan, Dan Solusi - Agustina; Suci Nur Insani; Adelia Januarti; Diva Agus Riyanti; Haura Faseha Afda; Haya Dzikra Anandisya (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study aims to analyze the effectiveness of Indonesia's immigration policy in addressing human trafficking as a form of transnational crime. Using a descriptive-analytical qualitative approach, this study explores immigration policy strategies and their implementation in the field. Data was obtained through a literature review of legal documents and official publications from relevant institutions. The results of the study show that although the government has adopted legal and non-legal policies to combat human trafficking, their implementation still faces various obstacles, such as limited human resources, lack of inter-agency integration, weaknesses in the information technology system, and legal loopholes related to human trafficking. In addition, Indonesia's geographical location as an archipelagic country further exacerbates the effectiveness of surveillance in border areas. This study recommends the need to strengthen specific regulations related to human trafficking, improve human resource and information technology capacity, optimize inter-agency coordination, and enhance the quality and security of travel documents. A comprehensive and integrated approach is necessary to ensure that immigration policies can be implemented effectively and sustainably in addressing the crime of human trafficking.